Control of heterointerface and strain mapping in Au catalyzed axial Si-Si1-xGex nanowires. Issue 1707 (7th July 2014) - Periwal, P.; Patriarche, G.; Latu-Romain, L.; Salem, B.; Bassani, F.; Baron, T.
ABSTRACT: Axial heterostructure nanowires with Si and SiGe segments have been grown using Au metal seed as catalyst by chemical vapor deposition (CVD) via vapor-liquid-solid process (VLS). We report on the effect of growth intervention on the droplet stability which in turn modifies NW morphology and interfacial abruptness. Growth stop of 2 minutes on transition from one material to another have been demonstrated to suppress reservoir effect by Au catalyst. The two SiGe/Si and Si/SiGe heterointerfaces are found to be assymetric. The former being diffused while the latter one is sharp. Furthermore, geometric phase analysis reports elastic deformation at the heterointerface. Nanowire undergoes rotation in both clock and anticlockwise direction at their sidewalls with an angle of 2.5° in order to accommodate this strain.